The best punctuation book, period. : a comprehensive guide for every writer, editor, student, and businessperson - Casagrande, June. (2014)
"This all-in-one reference is a quick and easy way for book, magazine, online, academic, and business writers to look up sticky punctuation questions for all styles including AP (Associated Press), MLA (Modern Language Association), APA (American Psychological Association), and Chicago Manual of Style. These days, writers wear many different hats: they write magazine and news articles, sales copy, online newsletters, books, and reports. It's hard to keep the punctuation style rules for each one straight--until now. This comprehensive reference from grammar guru June Casagrande is organized by punctuation type to give writers quick answers no matter what they're writing for. The Best Punctuation Book, Period provides clear answers to common questions about hyphenation, commas, apostrophes, numbers, and italics; a Punctuation A to Z section addressing commonly confused terms in one master list; and rulings from an expert Punctuation Panel on gray areas. With this resource in hand, writers will be able to craft polished, appropriate prose for every job in a flash"--
Keywords: English language -- Punctuation -- Handbooks, manuals, etc; English language -- Grammar -- Handbooks, manuals, etc; English language -- Rhetoric -- Handbooks, manuals, etc; LANGUAGE ARTS & DISCIPLINES / Grammar & Punctuation; REFERENCE / Writing Skills; LANGUAGE ARTS & DISCIPLINES / Reference